ANALISIS TITIK IMPAS (BREAK EVEN POINT) PENGGUNAAN LAMPU LED UNTUK PENERANGAN: STUDI KASUS GEDUNG TG UNIVERSITAS X DI SURABAYA - Junanik Idayani; Endah Asmawati; Marlina Marlina (Jurnal Bisnis Terapan, 2017)
Energy management, one of energy conservation, is activities in organizing data collection, analyzing, planning, implementing, monitoring, and evaluating energy use. The increasingly limited supply of energy raises the demand to think about how to use the lights so that the breakeven point of the product used can be optimally utilized. The basic principle is the efficient and rational use of energy without reducing the use of energy that is really necessary, in other words the use of needsbased. The scope of this study is limited to the calculation of the breakeven point of the use of 3 brands of LED lamps used for lighting that support the conservation of electrical energy. In the calculation of the break-even point, it is necessary to study the most efficient lamp brand. Therefore, in this study the efficiency level will be calculated using three different brands of LED lights, namely brands A, B and C. The study was conducted by noting the use of electrical energy for lighting on a space in the TG building that was turned on for 8-9 hours every day. The measurement results state that LED B-brand lamps are economically more sparingly 55% each month compared to other brands, and operational cost advantage occurred in the 78th month while other brands occurred in the 91st month..